Evaluating the Impact of Export Finance Support on Firm-Level Export Performance : Evidence from Pakistan - Defever, Fabrice; Riano, Alejandro; Varela, Gonzalo J. (World Bank, Washington, DC, 2020)
This paper evaluates the impact of two export finance support schemes, the Export Finance Scheme and the Long-Term Finance Facility for Plant & Machinery on firm-level export performance in Pakistan. These policies offer loans to exporters at concessionary interest rates to finance short-term working capital and long-term investment in machinery and equipment, respectively. The paper combines customs data with information on firms that participated in each scheme and the value of the loans they obtained between 2015 and 2017. Using matching estimators to control for the nonrandom selection of firms into the schemes, the analysis finds that the Export Finance Scheme and Long-Term Finance Facility for Plant & Machinery increased the growth rate of export sales by 7 and 8-11 percentage points, but they do not have a significant impact on the number of products that a firm exports or the number of foreign countries to which it sells to. A cost-benefit analysis shows that although both schemes deliver net benefits, they entail a substantial financial cost to Pakistan's central bank.